70th Anniversary Of The Lviv Scientific School Of Oncology - Bilynsky, B.T.; Shparyk, Ya.V.; Mryglotsky, M.M.; Lukavetskyy, N.O.; Volod’ko, N.A.; Litvinyak, R.I. (Experimental Oncology, 2016)
Contemporary development of scientific thought is fostered not by separate people but is a purposeful activity of a group of likeminded people armed with progressive ideas and modern technical equipment. Such schools appeared and work actively in the majo rity of research and educational establishments, clinics, and universities. The Lviv school established in 1945 by Professor H.P. Kovtunovych and developed by Professor A.I. Hnatyshak and his disciples can serve as an example of a successful school of oncology that continues its activity and yields scientific results. This school appeared not out of the thin air. Medieval Lviv could boast of the first university on the territory of the present-day Ukraine. Many discoveries and endeavors that made a beneficial impact on the development of medicine in Eastern Europe were made in this city. For historical reasons, the city of Lviv used to belong to different state formations (Austria-Hungary, Poland, the USSR; now it is a part of Ukraine), which could not but reflect on the staffing of doctor-researchers. This process acquired a special intensity in 1939–1945 when the research staff of the university changed substantially. Then, in 1945, H.P. Kovtunovych, the disciple of the prominent oncologist N.N. Petrov, came to Lviv and brought the ideas of St.-Petersburg oncology to the Lviv ground. The Lviv school was influenced by the two times Nobel Prize winner Marie Skłodowska Curie, who facilitated the initiation of oncological radiology in Lviv. The article contains data on research done by the disciples of Professors H.P. Kovtunovych and A.I. Hnatyshak. The first ever teaching chair of oncology in the USSR was founded in Lviv (1966), as well as the first Ukrainian hospice — an institution for palliative care for the oncological patients. The Lviv oncology center is one of the biggest and best-equipped oncology centers in Ukraine. An organic combination of theory and clinical practice has always been the guiding principle of the Lviv school of oncology. Presently, the Lviv school of oncology unites six doctors of sciences, a large collective of educators and researchers, as well as practitioners of the center of oncology. The school maintains close scientific and practical ties with oncologists of Ukraine as well as with leading oncological centers of Europe and America.